Implementasi Metode Scramble Untuk Meningkatkan Motivasi Belajar Bahasa Arab di MTs Futuhiyyah Bangorejo - Nasrullah, M Alaika; Iswahyudi (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2024)
The scramble method is a learning method that invites students to find answers and solve existing problems by distributing question sheets and answer sheets accompanied by available alternative answers. The aim of this research is to determine the application of the scramble method in increasing motivation to learn Arabic and to determine the evaluation of Arabic language learning outcomes after using the scramble method. This type of research is qualitative descriptive research. Researchers observed and interacted with informants by reviewing and searching for data by requesting documentation from the school. The results of research on the application of the scramble method show that the scramble learning method offers a solution with a fun learning concept as an effort to improve learning aspects including students' interest, motivation and Arabic language learning outcomes. And the evaluation results from research regarding the application of the scramble method are that students can complete the tasks given by the teacher well and correctly, as evidenced by the work results of each group reading or presenting the work results of each group in front of the class.